Identification of NPHS1 Genetic Variations in Cohort of Egyptian Patients with Congenital Nephrotic Syndrome - Samy, Amira; Elkaffas, Rasha; Fadel, Fatina; Mosaad, Nehad; Madani, Hanan (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Autosomal recessive variations in NPHS1 gene represent common cause of congenital nephrotic syndrome (CNS). The disease is characterized by considerable proteinuria presenting in the first 90days of life. CNS has a poor outcome and usually leads to end stage renal disease by 2-3 years of life. NPHS1 encodes the protein nephrin, expressed in inter-podocyte slit diaphragm. Aim of work: The main objective of this cross-sectional study was to perform the analysis of the NPHS1 gene in 24 Egyptian patients with CNS aiming to determine the molecular cause of the disease and to detect their phenotype/genotype correlations. Methods: Polymerase chain reaction followed by direct sequencing of exons (3,4,6,7,18,19) of NPHS1 gene was performed in 24 neonates with CNS with median age 25 days (1-90 day). Results: three pathogenic variants were detected in five patients. They were one frame shift variant in exon 19, one missense de novo variant in exon 6 and one In-frame deletion variant in exon 4. Three benign variants were seen in seven patients in exon and intron 3. Conclusion: although the number of patient included in the study is small, but the results of the study presented de novo likely pathogenic mutation in exon 6 not reported before in 2 patients and 2 reported pathogenic variants. Molecular diagnosis is advised to be performed early in the diagnosis of CNS to avoid unnecessary immunesupp-ression and start early suitable treatment.